Electronic health record system in the public health care sector of South Africa: A systematic literature review - Munyaradzi C. Katurura; Liezel Cilliers (AOSIS, 2018)
Background: South Africa is planning to implement the National Health Insurance (NHI) scheme in the near future. The NHI is intended to improve the accessibility of quality health care services for all South African citizens. For the NHI to achieve this objective, an electronic health record (EHR) system to register and track patients who visit different health care providers will have to be developed. Aim: To identify critical success factors for the implementation of EHRs in South Africa's public health care sector. Setting: This study reviewed studies on EHR implementation in African countries published between 2006 and 2017. Methods: The study made use of a systematic literature review to identify barriers to the implementation of EHRs in the public health care sector. Results: Fifteen articles were included in the study. The study identified technical, social and environmental barriers to the implementation of EHRs. The barriers could further be broken down into lack of supporting infrastructure; user training and commitment; political influence or strategy; legislation and regulations; and the lack of a framework for implementation and management of EHRs. The study suggests six main recommendations for the successful implementation of EHRs in South Africa's public health care sector. Conclusion: The study recommended investing in alternative infrastructure facilities, incentivising the health informatics field to attract and retain information and communication technology professionals and to encourage the participation of all stakeholders in the development process to develop context-relevant e-health implementation strategies, legislation and frameworks. Government should also allocate separate budgets for e-health projects.